O ponto de vista ficcional em O tigre de Bengala, de Elisa Lispector - Henrique, Joyce Kelly Barros (2020)
The general objective of this research is to analyze the fictional point of view in the short stories of O tigre de Bengala (1985), by Elisa Lispector, observing the interaction between the interiority of the female character and the representation of the external space. We analyzed four stories by the author (“Sangue no sol”, “O furto”, “A agonia de viver” and “Por puro desespero”); however, we weave relationships considering all the texts from the book, investigating points of approximation and differentiation. In the first part of this work, we present the production of Elisa Lispector, with regard to the narrative perspective. We also carried out a review of critical works about the author, published in newspapers, books and virtual platforms. The second chapter consists of a theoretical discussion, based on the North American line - Norman Friedman (2002), Percy Lubbock (1976), Henry James (2003), and Joseph Warren Beach (1932) -, which deals with the concepts of point of view, scene, narrative summary, distance, as well as the representation of thought in literature. For this theory, the framing of the action in the character's consciousness expands the scenic nature of the text (reducing the narrator's interferences) and turns the thought into an essential element for the interpretation of the literary narrative. In the third chapter, the critical reading shows that, in Elisa Lispector's stories, the characters' action is minimal and the inner monologue is the basic point of view; however, it coexists with frequent notations by observant and omniscient narrators. This combination allows immersion in the protagonist's thinking, without giving up a distant view of the scene, since space both triggers reflections and maintains a relationship of affinity, refusal, resignation, transformation and overcoming with the character. In this story, the inner monologue is a formal resource that supports the protagonists' self-assessment and provides them with a review/reformulation of their perspectives.